Alobar holoprosencephaly: a case report - Tjokorda Gde Agung Suwardewa; Ryan Saktika Mulyana; William Alexander Setiawan (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: Holoprosencephaly (HPE) is a rare congenital malformation of the brain; the incidence rate was 0.49-1.2 cases per 10,000-20,000 term births. HPE occurs due to failure of the prosencephalon division at the stage of brain development during the 4-5 weeks of pregnancy. Alobar HPE is one of the most severe types compared to other types. Most of the fetuses affected by this anomaly will die, and those born alive generally cannot survive for more than a year. This study presented a rare case of a baby with alobar HPE. Case report: A 33-year-old woman referred from Karang asem hospital Bali, G3P0020, 23 weeks gestation, has a poor obstetric history. The ultrasound examination results show no falx cerebri, even cerebellum and hypoechoic picture of the cerebrum. Ultrasound of the face was found a flat nose and hypotelorism. Termination at 28 weeks gestation, a baby boy was born 1000 g with the Apgar score 1-1. Multiple congenital abnormalities were found: flat nose, labiopalatoschizis, polydactyly manus dextra and omphalocele. Conclusion: Alobar HPE is a very rare congenital anomaly. The cause of the disease has not been fully explained. Current therapy is just supportive and has not been able to resolve the source of the problem. Alobar HPE disease has a poor prognosis.